A novel pre-synchronization control strategy for microgrid connections based on improved droop control. (November 2022) - Jiang, Wenbo; Li, Pan
Abstract: Microgrid control strategies based on traditional droop control often exhibit output voltage and frequency return errors. As such, this study proposes a novel pre-synchronization control strategy to improve both the accuracy and stability of voltage and frequency, suppress harmonics generated by an inverter, and reduce the control errors. First, an improved droop control strategy was proposed to automatically adjust the microgrid output voltage and frequency in order to achieve power sharing and suppress voltage harmonics. A pre-synchronization controller was then used to compensate for the angular frequency during droop control, based on deviations in output voltage and frequency between the microgrid and power grid. This ensured stability and smooth switching between the two grids. Finally, a series of numerical simulations were conducted with the Matlab/Simulink software. The simulated results exhibited a frequency fluctuation range of 49.95–50.02 Hz, and 49.5–50.2 Hz for traditional droop control. In addition, a voltage deviation of only ± 2.89% was observed from the nominal voltage (in both connected and islanded operation). The total harmonic distortion (THD) rate was 1.50% when the microgrid was connected to the power grid and 2.57% for traditional droop control. These results suggest the proposed control strategy to be highly effective and reliable.